ANALYSIS OF TRANSACTIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT. CITRA MULIAPERKASADI KENDARI CITY, SOUTHEAST SULAWESI - Tresya Kayangan; Eka Fitra Ramadani; Yudie Andrew Pratama Lumoindong (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine and analyze 1) AnalysisofTransactional Leadership Style on Employee Performance at PT. Citra Mulia Perkasa in Kendari City, Southeast Sulawesi and2) Supporting and Inhibiting Factors of Transactional LeadershipStyleAnalysis on Employee Performance at PT. Citra Mulia PerkasainKendari City, Southeast Sulawesi. This study uses qualitativedescriptive using the concept of interactive data analysis. Informantsin this study consisted of employees of PT. Citra Mulia Perkasa. Withdata collection techniques of observation, interviews anddocumentation. The results of the study indicate that thetransactional leadership style applied by PT. Citra Mulia Perkasahasnot run optimally because the demands of the work arenot comparable to the results obtained by employees, as well astheexistence of a work culture that is not in accordance withtheregulations or standard operating procedures for workers. Thesefindings are expected to improve the regulations in force at PT. CitraMulia Perkasa and become a learning experience for leaderstoimprove their attitudes towards their employees